Ethnoornithology and Bird Conservation in Afro-descendant Communities in the Brazilian Caatinga - Aurea Palloma Bezerra Barbosa Veras; Cauê Guion de Almeida; Lorena Lima de Moraes; Alexandre M. Fernandes (Ethnobiology Letters, 2022)
This paper investigates relationships between birds and the inhabitants of Afro-descendant communities in the Caatinga of northeastern Brazil, paying particular attention to conservation. Near the Refúgio de Vida Silvestre da Serra do Giz wildlife reserve, we interviewed 55 residents using semi-structured forms combined with free interviews and informal conversations. Residents reported 121 species in 43 families and 21 orders. They recounted what they knew about nesting, reproductive and social behaviors, diet, and bird conservation. The lack of reporting on several species of birds known from the Serra do Giz was probably because those birds are absent due to hunting and habitat destruction. This study demonstrates the importance of conducting ethnobiological studies for bird conservation and to record local traditional knowledge.